2005
DOI: 10.5902/198050981730
|View full text |Cite
|
Sign up to set email alerts
|

Himenópteros parasitóides coletados em povoamento de <i>Eucalyptus grandis</i> e mata nativa em Ipaba, estado de Minas Gerais.

Abstract: A composição e a frequência da fauna de himenópteros parasitóides foi estudada em reflorestamento de Eucalyptus grandis W. Hill ex. Maiden e mata nativa, empregando-se 11 armadilhas Malaise em um transecto eucalipto-mata nativa de março de 1997 a março de 1998. Foram coletados 2.099 indivíduos de nove superfamílias e 26 famílias desse grupo. As famílias mais abundantes foram Ichneumonidae, Braconidae, Scelionidae e Eulophidae com 577, 452, 374 e 185 indivíduos respectivamente. O número de parasitóides foi maio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
1
6
0
2
Order By: Relevance
“…ns = não significativo; n = 24. positivos da presença de remanescentes de vegetação nativa na abundância de parasitóides (Bragança et al 1998a, Freitas et al 2002, dall'oglio et al 2003 e nas taxas de parasitismo de pragas em eucaliptais (Murta et al 2008). da mesma forma, Sperber et al (2004) verificaram influência positiva da riqueza de árvores de vegetação remanescente em plantios de cacau (Theobroma cacao, Sterculiaceae) sobre a riqueza de famílias de parasitóides (Braconidae, Ichneumonidae, Encyrtidae, Scelionidae, entre outros).…”
Section: Discussionunclassified
“…ns = não significativo; n = 24. positivos da presença de remanescentes de vegetação nativa na abundância de parasitóides (Bragança et al 1998a, Freitas et al 2002, dall'oglio et al 2003 e nas taxas de parasitismo de pragas em eucaliptais (Murta et al 2008). da mesma forma, Sperber et al (2004) verificaram influência positiva da riqueza de árvores de vegetação remanescente em plantios de cacau (Theobroma cacao, Sterculiaceae) sobre a riqueza de famílias de parasitóides (Braconidae, Ichneumonidae, Encyrtidae, Scelionidae, entre outros).…”
Section: Discussionunclassified
“…Chalcidoidea and Ichneumonoidea are the most important groups of the Hymenoptera order in the forests where they parasitize eggs, larvae, pupae and adults of insects, mainly of the orders Coleoptera, Lepidoptera, Diptera and Homoptera (Berti Filho, 1985). The families Ichneumonidae, Braconidae, Scelionidae and Eulophidae have been the most abundant ones in eucalyptus plantations (Dall'Oglio et al, 2003). The family Eulophidae presents 283 genera and 3977 species in tropical and temperate areas as endoparasitoids or ectoparasitoids; idiobiontes or koinobiontes; solitary or gregarious; primary or hiperparasitoids; specialists or generalists and many of these species have been studied and used with success in programs of biological control (Noyes, 1998;Gauthier et al, 2000;Hansson, 2004).…”
mentioning
confidence: 99%
“…Previous research has shown that Hymenoptera natural enemies were more abundant at the edge of eucalyptus plantations adjacent to native forests and inside native forests than inside eucalyptus plantations (Freitas et al 2002). The abundance of Hymenoptera parasitoids was also higher at the edge of native vegetation adjacent to eucalyptus plantations compared with their abundance inside these plantations (Dall'oglio et al 2003). Strips of native vegetation can increase the diversity and abundance of natural enemies and their effectiveness in biological control Freitas et al 2002).…”
Section: Discussionmentioning
confidence: 98%